Gamma-aminobutyric acid (GABA) production by potential probiotic strains of indigenous fermented foods origin and RSM based production optimization. (15th February 2023) - Devi, Palanisamy Bruntha; Rajapuram, Dileep Reddy; Jayamanohar, Jabastin; Verma, Manika; Kavitake, Digambar; Meenachi Avany, Bargavi A.; Rani, Potunuru Uma; Ravi, Ramasamy; Shetty, Prathapkumar Halady
Abstract: The study aimed to evaluate the γ-aminobutyric acid (GABA) producing lactic acid bacterial strains of fermented food origin to be used as potential psychobiotic. A total of 268 isolates were screened for GABA production using the pH indicator method. Five of the isolates were identified as potential GABA producers and were shortlisted further for confirmation of GABA production by NMR and HPLC analysis. One of the strains (G2), identified as Weissella confusa showed the highest production of GABA (246.2 mg/L) while the remaining strains produced only trace amounts. These five strains were assessed for safety and probiotic properties. The strain G2 exhibited the most prominent probiotic properties. It showed good tolerance towards pH(2 and 3), bile salt(0.3–1%), gastro-intestinal fluid, NaCl(1–4%), phenol(0.4–0.6%), auto-aggregation(83%), strong hydrophobicity to xylene(70%) and chloroform(78%), significant antimicrobial activity, susceptibility to antibiotics and strong adherence to Caco-2 cells. From the optimization of culture conditions for GABA production by RSM based approach, G2 was found to produce 293.33 mg/L with a 34h fermentation time, 29.1 °C temperature, and at 1% mono-sodium glutamate concentration. Further studies are needed to assess the efficacy and stability of the isolate in the food matrix and in vivo gut environment, to utilize it as a potential psychobiotic. Highlights: γ-aminobutyric acid (GABA) producing bacteria were isolated from fermented foods. 5 strains were shortlisted for GABA production by NMR and HPLC analysis. Weissella confusa G2 showed strong probiotic properties. Strain G2 showed highest GABA production of 293.33 mg/L using statistical approach. Strain G2 could pave way for the development of psychobiotics.